Successful event management : a practical handbook - Shone, Anton; Parry, Bryn, 1961- (Andover, Hampshire : Cengage Learning, 2010)
This work is a guide to organizing major events such as festivals, parties, concerts, weddings, and conferences. It includes photocopiable forms that will help readers to plan and budget, and case studies and websites to learn from.
The events business -- An introduction to events -- The market demand for events -- The events business: supply and suppliers -- Social, economic, political and development implications, 2: Managing events -- Making a start and planning the event -- Financial management and the budget -- Event logistics and supplies -- Marketing and public relations for events -- Risk management and legalities -- Event project management and set up issues -- The organization manager and the team: during the event -- Close-down, evaluation and legacies
Includes bibliographical references and index
Keywords: Special events -- Management; Special events -- Planning